2005
DOI: 10.1037/0278-6133.24.6.579
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of posttraumatic stress disorder following cancer.

Abstract: This study investigated the predictors of posttraumatic stress disorder (PTSD) following a diagnosis of cancer. Individuals who were recently diagnosed with 1st onset head and neck or lung malignancy (N = 82) were assessed within 1 month of diagnosis for acute stress disorder (ASD) and other psychological responses including depression; individuals were reassessed (N = 63) for PTSD 6 months following their cancer diagnosis. At the initial assessment ASD was diagnosed in 28% of participants, and 22% met criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 44 publications
7
77
2
1
Order By: Relevance
“…In contrast, self-blame was unrelated to the severity of PTSD symptoms at both time points. The present results are similar to those reported in other medical contexts by Agar et al (2006), in relation to spinal cord injuries, and by Kangas et al (2005), in relation to cancer diagnosis. However, these results can be contrasted with those reported by Foa et al (1999) who found significant correlations between all three cognitive appraisals and the severity of PTSD symptoms in a sample of trauma survivors (including accidents, non-sexual assaults, sexual assaults, and illness).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In contrast, self-blame was unrelated to the severity of PTSD symptoms at both time points. The present results are similar to those reported in other medical contexts by Agar et al (2006), in relation to spinal cord injuries, and by Kangas et al (2005), in relation to cancer diagnosis. However, these results can be contrasted with those reported by Foa et al (1999) who found significant correlations between all three cognitive appraisals and the severity of PTSD symptoms in a sample of trauma survivors (including accidents, non-sexual assaults, sexual assaults, and illness).…”
Section: Discussionsupporting
confidence: 93%
“…Considering studies in medical contexts, Angar, Kennedy and King (2006) found that negative cognitions about the self and the world, but not self-blame, were associated with the severity of PTSD symptoms among a sample of patients with spinal cord injuries. Similar results have been reported by Kangas et al (2005) who found that negative cognitions about the self and the world assessed within one month of cancer diagnosis were associated with the severity of PTSD symptoms six months following diagnosis, whereas the correlation between self-blame and PTSD severity was non-significant. These studies provide initial evidence that the cognitive appraisals outlined by Foa et al (1999) are Stroke and PTSD 7 associated with PTSD symptom severity, although the use of cross-sectional and retrospective designs is a limitation of some of this research.…”
Section: Introductionsupporting
confidence: 89%
“…One study controlled for pre-existing dissociative tendencies (Murray, Ehlers, & Mayou, 2002) and 1 for personality traits (Holeva & Tarrier, 2001). Kangas et al (2005) found a strong correlation between cancer related PTSD and dissociative reactions upon receiving the diagnosis in a rather small sample of cancer patients (N=63). Among many other variables assessed, PD was the strongest predictor of PTSD severity and caseness.…”
Section: General Characteristics Of the Studiesmentioning
confidence: 82%
“…However, 2 of the 4 studies that explicitly included subjects suffering from (mild) TBI repeated the reported analyses excluding the TBI-subjects without affecting the results (Marshall & Schell, 2002;Wittmann et al, 2006). Four studies excluded subjects with TBI, the remaining 9 studies did not assess or report on TBI; for 4 of them it can be assumed that no TBIcases were included (Bennett et al, 2002;Kangas et al, 2005;Koopman et al, 1994;Van Loey et al, 2003).…”
Section: As Regards Physical Injury the Issue Of Traumatic Brain Injmentioning
confidence: 99%
See 1 more Smart Citation